The Role of Evaluation in the Selection of Learning Materials for a Dynamic Curriculum - Sri Handayani, Winda; Alfia, Ninda; Hariyatun, Hariyatun; Muamaroh, Muamaroh; Ratih, Koesoemo (Samudra Publisher, 2025)
This study aims to explore how teachers evaluate and select appropriate teaching materials to ensure their alignment with learning objectives and student needs. Using a descriptive qualitative approach, data were collected through document analysis and structures interviews with teachers. The analysis focused on the criteria used in the evaluation process, challenges faced in selecting materials, and strategies to overcome these challenges. The results indicate that teachers prioritize the relevance of teaching materials to students’ levels of understanding and learning objectives. However, they often face constraints such as limited budgets, restricted access to quality mterials, and time constraints for conducting evaluations. Despite these challenges, teachers demonstrate creativity by adapting existing materials and utilizing local resources. This study concludes that evaluation play a crucial role in ensuring the quality of teaching materials, while creative and flexible approaches help teachers address challenges effectively. These findings undercore the importance of integrating evaluation and innovation in teaching material selection to enhance the teaching and learning process within a dynamic curriculum framework.